Jasiri, study companion robot for the neurodivergent - Lim, Chloe Ke Yee (Nanyang Technological University, 2023)
As more awareness is being brought towards inclusivity and mental health awareness, more attention is being brought into providing strong support towards those with special needs. For the neurodivergent, their brains develop atypically, thus they will see and process the world differently from the neurotypical. Without proper structure, these individuals can find it difficult to navigate and keep up with what is considered normal. It can lead to them feeling overwhelmed and struggling in managing tasks effectively. Furthermore, without guidance, it may lead to them feeling isolated as they watch themselves fall behind their neurotypical peers. Jasiri aims to be a study companion robot like no other, being easy to use and affordable. Integrating both software and hardware, the system is made to be simple and be interactive to the majority of neurodivergent individuals, providing companionship and guidance they need. The overall system features: - Using Google ML Kit for face detection - Bluetooth connection for the phone to function wirelessly - mBot to control hardware components as a unit to be the perfect companion.